Belief and Investing: Preferences and Attitudes of the Faithful - Mark Brimble; Victoria Vyvyan; Chew Ng (Australasian Accounting, Business and Finance Journal, 2013)
This Australian study seeks to better understand the disparity between the positive attitudes towards Socially Responsible Investing (SRI) and the level of investment in SRI (Saulwick & Associates 2001; Watmore & Bradley 2001; Williams 2007; Arjalies 2010), by examining both the attitudes to SRI and the investment choices that are made. It is hypothesised that those who are more committed to religious belief principles are more likely to invest in SRI. To test this 322 people from two large Queensland organisations were surveyed in relation to their investment attitudes and preferences. Results show that those who are more religious are no more likely to invest in SRI, and that the level of importance placed on SRI and financial criteria are similar in most instances for the more and less religious. In addition, women who are religious place more importance on conservative general investment criteria than less or non-religious women.
Keywords: Socially Responsible Investing; Decision Making; Conjoint Analysis; Religion